The Money Scripts Related to the Use and Trust of Investment Advice - Travis L Sholin; Han Na Lim; Miranda Reiter; Efthymia Antonoudi; Meghaan Lurtz (Journal of Financial Therapy, 2021)
This study examines the association between four money scripts (i.e., money avoidance, money worship, money status, and money vigilance) and the use of investment advice and trust in that advice from a variety of sources (i.e., family and friends, financial software, financial professionals, and one’s own research). Using primary data, we found that money avoidance was negatively associated with trust in professional financial advice. Money worship is positively associated with receiving investment advice from financial software and doing one’s own research. Money status was negatively associated with trusting one's own research. Money vigilance was positively associated with using a financial professional for investment advice and trusting advice from a financial professional and family and friends. This study's findings provide implications for financial professionals and researchers focused on helping consumers with different money attitudes seek investment advice, utilizing narrative financial therapy and financial education.
Keywords: trust; investment advice; money scripts